Computer-Based On-Line Assessment of Sterilizing Value for Canned Food - Montip Chamchong,; Vilasinee Sangsom,; Nuttakorn Charoeamkitti, (Agriculture and Natural Resources, 2007)
Heating of canned food is to prolong shelf life and provide safety to the consumer while trying to maintain product quality. Sterilizing value or lethality process (Fo) is well accepted as an indicator for evaluating optimum thermal process time. Software and hardware used in the country for process control/design or validation are all imported. The study and development of local devices for computerbased on-line assessment of sterilizing value for canned food was the objective of this research. Design of the program for interfacing and processing to obtained on-line time-temperature history data was written by Visual Basic 6.0. This program displayed heat penetration curve during sterilizing graphically and also dynamically analyzed the data for accomplished Fo from all thermocouple probes in every 4.5 seconds. The accomplished Fo was calculated by general method and it was kept on recalculating until being reached the specified target Fo of that particular product. The program then would display warning message for the operator to shut off steam but the calculation still went on during cooling. The demonstration of such a computer-based on-line assessment with concentrated pineapple juice for process design and heat distribution in retort could be obtained.